Implementasi Model Pembelajaran Creative Problem-Solving pada Mata Pelajaran Dasar-dasar Ketenagalistrikan - Mursyida, Alfiana; Usmeldi, Usmeldi (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2024)
Experts have created numerous learning models to be applied during the learning process; however, not all learning models are suitable for every subject and student. This research implements the Creative Problem-Solving learning model and aims to determine the results of implementing the Creative Problem-Solving model in the subject of Fundamentals of Electrical Engineering at SMK Negeri 1 Tanjung Raya. This type of research uses a quantitative pre-experimental approach with a one-group Pretest-Posttest research design. The subjects of this research are 25 students from class X TITL 1 at SMK Negeri 1 Tanjung Raya. The data collection techniques used in this research include research instruments in the form of Pretest and Posttest essay questions to collect student learning outcome data and questionnaires to gather data on students' responses to the implementation of the Creative Problem-Solving learning model. These research instruments must be tested before being used as research instruments. The data analysis techniques used to determine the implementation of this learning model are classical completeness test, N-gain Score test, and descriptive analysis of the implementation response. The students' responses after the application of the learning model indicate a tendency towards positive responses, and there is an improvement in learning outcomes following the implementation of the Creative Problem-Solving model.